Immunosuppressive strategies in lung transplantation - Chung, Paul A. (Ann Transl Med, 2020)
Lung transplantation is a viable option for those with end-stage lung disease which is evidenced by the continued increase in the number of lung transplantations worldwide. However, patients and clinicians are constantly faced with acute and chronic rejection, infectious complications, drug toxicities, and malignancies throughout the lifetime of the lung transplant recipient. Conventional maintenance immunosuppression therapy consisting of a calcineurin inhibitor (CNI), anti-metabolite, and corticosteroids have become the standard regimen but newer agents and modalities continue to be developed. Here we will review induction agents, maintenance immunosuppressives, adjunctive therapies and other strategies to improve long-term outcomes.